The Implementing Author’s Vivid Speculation of the Technologically Advanced Era in the “I Robot” By Isacc Asimov - Usmonova Zarina Habibovna (Genius Journals, 2022)
This article provides critical analysis of “I Robot” by Isaac Asimov from comparative view, showing the differences of the events and robots written in the book with the ones in the real world. It supplies fragments from the “I Robot” and analyzes the very excerption if it is correct and pertinent prediction mentioned by I. Asimov. It gives relevant information about gadgets and feasible dominance of robots over humanity in both book and this technological era.
Keywords: Robot; robopsychology; artificial intelligence; dominancy